New species Pseudocercospora and new records from Thailand - Jeerapa Nguanhom (2018)
© 2017, Chiang Mai University. All rights reserved. Pseudocercospora is a large cosmopolitan genus of plant pathogenic fungi that are commonly associated with leaf and fruit spots as well as blights on a wide range of plant hosts. Three new Pseudocercospora species examined in the present research were collected and isolated in Thailand during a study of Mycosphaerella and related genera. These species include Pseudocercospora kopsii, P. mitracarpi and P. pericampylii, and 17 other species and represent new records for Thailand.